Pengaruh Penggunaan Model Kooperatif Tipe Team Assisted Individualization (TAI) dalam Pelajaran PKn di Sekolah Dasar - Reinita Reinita; Eci Eci (Pedagogi: Jurnal Ilmu Pendidikan, 2018)
This research aims to know the effect of the use of cooperartive learning model of type Team Assisted Individualization (TAI) to the result of learning PKN student class IV SD Pembangunan Laboratorium UNP. This Type of research is quasi eksperment. The Population in this study is class IV SD Pembangunan Laboratorium UNP with samples of class IV A dan IV B consisting of 20 and 18 students. Based on the result of t test calculation obtained t value = 2,325 and price t table = 2,042. This proves that the use of cooperative learning model type of TAI effect on the learning outcomes PKN class IV SD Pembangunan Laboratorium UNP.